2014
DOI: 10.1007/s00221-014-4093-8
|View full text |Cite
|
Sign up to set email alerts
|

Walking in high-risk settings: Do older adults still prioritize gait when distracted by a cognitive task?

Abstract: When a cognitive and a motor task like walking or keeping one's balance are performed concurrently, performance usually deteriorates. Older adults have often been shown to prioritize their motor performance in such dual-task situations, possibly to protect themselves from falls. The current study investigates whether these prioritization behaviors can still be observed when several challenges are combined. Younger (20-30 years old) and older adults (60-70 years old; n = 24 in each group) were asked to walk thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Based on the postulate that the attentional system has a limited pool of resources [2], it is expected that the concomitant performance of different tasks competing for the same resources could be worse with respect to the independent performance of each task. Significant decrements in gait and/or cognitive performance are observed in older adults when cognitive tasks are performed while walking [3, 4]. Such performance decrements are referred to as DT interference and commonly evaluated as the difference between the single and DT performance in relation to the first (DT cost).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the postulate that the attentional system has a limited pool of resources [2], it is expected that the concomitant performance of different tasks competing for the same resources could be worse with respect to the independent performance of each task. Significant decrements in gait and/or cognitive performance are observed in older adults when cognitive tasks are performed while walking [3, 4]. Such performance decrements are referred to as DT interference and commonly evaluated as the difference between the single and DT performance in relation to the first (DT cost).…”
Section: Introductionmentioning
confidence: 99%
“…Findings with respect to the posture first hypothesis, however, have been mixed (Gerin-Lajoie et al 2005; Lindenberger et al 2000). It is noteworthy that failure to demonstrate this preference (Schaefer et al 2015) may be attributed to limitations of available cognitive resources in older adults (Holtzer et al 2011). Furthermore, in neurological conditions, such as Parkinson’s disease, patients are reported to use the posture second strategy where cognitive tasks are prioritized over walking, leading to an increase in falls risk (Bloem et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1) for other tasks. Recent studies reported slower self-selected walking speeds in visuolocomotor situations (e.g., walking on a narrow path [26] or a sequence of stepping stones [27]) compared to unconstrained walking, for young and older adults alike. This was interpreted as an adaptive strategy to favor task performance relative to the visual context [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported slower self-selected walking speeds in visuolocomotor situations (e.g., walking on a narrow path [26] or a sequence of stepping stones [27]) compared to unconstrained walking, for young and older adults alike. This was interpreted as an adaptive strategy to favor task performance relative to the visual context [26,27]. Given our current results, it thus seems likely that older adults slowed down their preferred walking speed to increase the available time for visuolocomotor control [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation